Meningeal Tertiary Lymphoid Tissues and Multiple Sclerosis: A Gathering Place for Diverse Types of Immune Cells during CNS Autoimmunity - Pikor, Natalia B.; Prat, Alexandre; Bar-Or, Amit; Gommerman, Jennifer L. (Frontiers in Immunology, 2016)
Collections of leukocytes in the meningeal space have been documented in Multiple Sclerosis (MS). These meningeal aggregates, which in the context of other autoimmune diseases have often been termed Tertiary Lymphoid Tissues (TLT), have been associated with sub-pial cortical damage and disease progression. However, the key molecular and cellular signals required for their formation and maintenance, remain unclear. Herein we review TLT structures in other disease states in order to provide a framework for understanding these structures in the MS meninges. We then assess the evidence that the meningeal compartment serves as an important nexus for immune cells as well as a location for drainage of antigen into the cervical lymph node compartment. Extrapolating what is known about the molecular and cellular cues that initiate the formation of leukocyte aggregates in non-lymphoid tissues, we speculate on what signals lead to the formation and maintenance of meningeal TLT structures. Referring to the animal model of MS (Experimental Autoimmune Encephalomyelitis - EAE), we also explore what is known about these structures in supporting B cell and T cell responses during neuroinflammation. Lastly, we examine the evidence that connects these structures to ongoing neuropathology. Collectively, our review points to the meningeal compartment as an important player in neuroinflammatory processes. Moreover, we hypothesize that in order to gain insights into pro- and anti-inflammatory properties of lymphocytes in MS, one must understand the cellular scaffolds that support lymphocyte retention within the meninges, thus highlighting the importance of non-immune cells (stromal cells) in the neuroinflammatory process.